Ground-Based Analogs for Human Spaceflight - Pandiarajan, Meenakshi; Hargens, Alan R. (Frontiers in Physiology, 2020)
This mini-review provides an updated summary of various analogs for adaptations of humans to the microgravity of space. Microgravity analogs discussed in this paper include dry immersion, wet immersion, unilateral lower-extremity limb suspension, head down tilt, and supine bed rest. All Earth-based analogs are imperfect simulations of microgravity with their own advantages and disadvantages. This paper compares these five frequently used microgravity analogs to offer insights into their usefulness for various physiological systems. New developments for each human microgravity analog are explored and advantages of one analog are evaluated against other analogs. Furthermore, the newly-observed risk of Spaceflight Associated Neuro-Ocular Syndrome (SANS) is included in this mini review with a discussion of the advantages and disadvantages of each method of simulation for the relatively new risk of SANS. Overall, the best and most integrated analog for Earth-based studies of the microgravity of space flight appears to be head-down tilt bed rest.